Art as an effective form of cultural diplomacy (Journal of Philosophy Culture and Political Science, 2018)
The cultural affairs start to gain greater significance in the field of international relations. The article examines some of the key issues pertaining to art as a form of cultural diplomacy. In the light of the new global context, art is becoming an effective tool of cultural dipomacy. However, there are multiple issues limiting the effectiveness and sustainability of the programs, including the ‘soft’ power ambiguity, lack of institutional support, estimation difficulties, and the interplay between the key agents of cultural diplomacy. Key words: culture, cultural diplomacy, cultural exchanges, art, Globa lization, “soft” power, international relations.